Mędrzec – ideał dla wybranych? Tożsamość mędrca w Księdze Syracha - Pudełko, Jolanta Judyta (Warszawskie Studia Teologiczne, 2018)
To be a scribe and a sage was an ideal for men of Israel who desired to approach God and participate in his wisdom. Was it possible for everybody? The article presents, in a synthetic way, the identity of the sage as described in the Book of Sirach. The calling of the sage implies a long and hard process of formation and growth, which continues until the end of his life. This calling, while requiring preparation and effort, must not be reduced to one of many – perhaps a bit more prestigious – professions and jobs. In his Book, Sirach shares with the reader his personal experience of acquiring wisdom and “becoming” a sage. He points at hard beginnings, at enjoyment of the fruit of his efforts, and finally at the necessity for sharing his acquired and received wisdom. It is only after the sage shares his wisdom with his disciples that he achieves the fullness of his identity. He then becomes a spiritual father of his disciples, sharing his wisdom as well as his own life and experience of God.